Meningkatkan Kemampuan Berbicara Siswa melalui Debat Aktif - Yulizar, Ismi; Hasibuan, Siti Aminah (Titian: Jurnal Ilmu Humaniora, 2022)
Abstract: This study presents research about improving students’ speaking skill through active debate of the twelfth grade. Speaking is one of four elements in english and it can improve english skill for the students. Active debate is one of the methods to increase the speaking skill because debate is dominant of speaking and it can practice fluently. This research aimed to describe the using active debate learning model to improve the students’ speaking skill and to identify how much students’ speaking skill improvement after being taught by using active debate learning model. The methodology of this research is a classroom action research which consisted of 2 cycles. The subject of this research is the tewltfh grade at SMK S Al-Bukhary consisted of 21 students. The researcher collected the source of the data related to this research from observation and test which was conducted in every cycle. The researcher used intrument data from obervation checklist, test, and documentation. Based on the collected data, the information gap proved effective in improving both the students’ speaking skills and the learning process of English speaking. The detailed results were as follows: Cycle 1 the percentage of speaking aspect is 54,34% and the average value is 54,38. In cycle II, the percentage of speaking aspect is 74,58% and the average value is 54,61. The result of the researcher is improvement with value 20,23. Therefore, it can be concluded that through active debate can improv the students’ speaking skill.  Keywords : improving, students’ speaking skill, active debate